Exploiting the locality of periodic subsystem density-functional theory: efficient sampling of the Brillouin zone. (24th November 2015) - Genova, Alessandro; Pavanello, Michele
Abstract: In order to approximately satisfy the Bloch theorem, simulations of complex materials involving periodic systems are made times more complex by the need to sample the first Brillouin zone at points. By combining ideas from Kohn–Sham density-functional theory (DFT) and orbital-free DFT, for which no sampling is needed due to the absence of waves, subsystem DFT offers an interesting middle ground capable of sizable theoretical speedups against Kohn–Sham DFT. By splitting the supersystem into interacting subsystems, and mapping their quantum problem onto separate auxiliary Kohn–Sham systems, subsystem DFT allows an optimal topical sampling of the Brillouin zone. We elucidate this concept with two proof of principle simulations: a water bilayer on Pt[1 1 1]; and a complex system relevant to catalysis—a thiophene molecule physisorbed on a molybdenum sulfide monolayer deposited on top of an α -alumina support. For the latter system, a speedup of 300% is achieved against the subsystem DTF reference by using an optimized Brillouin zone sampling (600% against KS-DFT).